PRODUCTION AND INNOVATIVE INFRASTRUCTURE FOR ATTRACTION THE HIGH-TECH BUSINESSES (Вестник университета)
The article systematizes and reveals the main forms of production and innovation infrastructure that promote investment, increase of technological level of production, export expansion, improvement of the skill level of employees and regional development. The innovative potential of the region is formed through the interaction of social, political, institutional and social factors as well as the impact of the environment within which economic agents operate. Special attention is paid to special economic zones, territories of advanced development, industrial parks, clusters and technoparks. The features of their functioning are presented.